MultiMedia modeling. 24th International Conference, MMM 2018, Bangkok, Thailand, February 5-7, 2018, Proceedings /: 24th International Conference, MMM 2018, Bangkok, Thailand, February 5-7, 2018, Proceedings. Part I : ([2018]) - Unknown
No abstract available